2018
DOI: 10.19173/irrodl.v19i3.3662
|View full text |Cite
|
Sign up to set email alerts
|

Open Educational Resources: Challenges and Opportunities in Indian Primary Education

Abstract: Education is a fundamental human right, yet one fifth of the world’s population lives with poor literacy. India is home to the largest number of illiterate people, with infrastructural, cultural, and socio-economic factors hindering equitable access to quality education. Due to the rapidly growing technology and Internet usage in the country, open educational resources (OER) are increasingly being used as a vital tool to help transcend barriers to child literacy, also aiding in educational attainment. While an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…OER promotes open pedagogy and open learning. Hence, OER-based blended learning improves teaching quality, enhances the quality of education and provides pedagogical benefits, which are reported in six studies (Bansal et al , 2013; Belikov and Bodily, 2016; Ganapathi, 2018; Ngimwa and Wilson, 2012; Pounds and Bostock, 2019; Tlili et al , 2020).…”
Section: Characteristics Of the Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…OER promotes open pedagogy and open learning. Hence, OER-based blended learning improves teaching quality, enhances the quality of education and provides pedagogical benefits, which are reported in six studies (Bansal et al , 2013; Belikov and Bodily, 2016; Ganapathi, 2018; Ngimwa and Wilson, 2012; Pounds and Bostock, 2019; Tlili et al , 2020).…”
Section: Characteristics Of the Studiesmentioning
confidence: 94%
“…A total of 11 studies reported that lack of awareness is the biggest challenge of OERs as most of the users are unaware of OERs and it could be another contributing factor to the non-adoption of OERs in higher education settings. Moreover, most of the academics were unaware of the license that underpins copyright exploitation (Bansal et al , 2013; Ganapathi, 2018; Hassall and Lewis, 2017; Henderson and Ostashewski, 2018; Hu et al , 2015; Kumar et al , 2021; Ngimwa and Wilson, 2012; Pounds and Bostock, 2019; Tang, 2020; Tlili et al , 2020; Wright et al , 2019).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also help develop knowledge and they are easily used when digitized (Al-tal, 2013). However and according to Yuan et al (2008), Falconer, Littlejohn, McGill, andBeetham (2016), Dutta (2016), and Ganapathi (2018), OER encounter many challenges and obstacles. They include the lack of the policies that assert the pedagogical and educational innovations in the organizational change of higher education institutions, the difficulty to have a balanced approach to effective cross-cultural communication, as well as the lack of the communication and cooperation between the institutions and the developers of teachers and students.…”
Section: Challenges and Opportunities Of Applying Oermentioning
confidence: 99%
“…According to Yang and Cotera (2011), the utilization and production of OER underline a real need for establishing an educational city that allows for the exchange of the best experience and practices to create a new learning system that helps embody lifelong learning across academic education. Dutta (2016) and Ganapathi (2018) report that OER provide many educational opportunities for the teacher, the student, and the educational process as a whole. They reinforce the individual's learning and teaching, develop a mechanism for improving and enriching the quality of general and higher education, and create an intellectual capital for innovation and creativity in various fields.…”
Section: Challenges and Opportunities Of Applying Oermentioning
confidence: 99%